2018
DOI: 10.1049/iet-nbt.2017.0295
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of biologically synthesised bismuth nanoparticles against HT‐29 cell line

Abstract: This study was purposed to examine the cytotoxicity and functions of biologically synthesised bismuth nanoparticles (Bi NPs) produced by sp. SFG on human colon adenocarcinoma cell line of HT-29. The structural properties of Bi NPs were investigated using transmission electron microscopy, energy dispersive X-ray, and X-ray diffraction techniques. The cytotoxic effects of Bi NPs were analysed using flow cytometry cell apoptosis while western blot analyses were applied to analyse the cleaved caspase-3 expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Interestingly, Shakibaie et al discoveries supported this current study, in which bismuth nanoparticles possessed moderate radical scavenging properties but might also stimulate oxidative stress in facilitating cell killing mechanisms. 85 In a report of irradiated Bi 2 Se 3 -treated mice, it was indicated that the ROS induced in the blood could be oxidized by the nanoparticles. 86 The anti-radical properties of BiONPs could be instigated by the deficiency of oxygen in the material's surface, which might undergo a combination with the ROS.…”
Section: Intracellular Ros Induced By Radiation With Bb Bc and Bcb mentioning
confidence: 99%
“…Interestingly, Shakibaie et al discoveries supported this current study, in which bismuth nanoparticles possessed moderate radical scavenging properties but might also stimulate oxidative stress in facilitating cell killing mechanisms. 85 In a report of irradiated Bi 2 Se 3 -treated mice, it was indicated that the ROS induced in the blood could be oxidized by the nanoparticles. 86 The anti-radical properties of BiONPs could be instigated by the deficiency of oxygen in the material's surface, which might undergo a combination with the ROS.…”
Section: Intracellular Ros Induced By Radiation With Bb Bc and Bcb mentioning
confidence: 99%
“…ZnO NPs have also proved to induce the expression of the genes attributed to ROS generation, OS damage and apoptosis such as Bax, p53, caspase-3 and caspase-9 [35]. Another study has also demonstrated that biogenic NPs (tellurium nanorods) induced necrosis or late apoptosis without altering the activity of caspase pathway [22]. Therefore, both apoptosis and necrosis may occur after exposure to NPs.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative mechanism and rise of OS indices were also observed as being involved in inducing cellular and organs toxicity after exposure to NPs, leading to apoptosis or necrosis [5,22]. The dual protective and toxic role for Zn-containing compounds based on the dose administered has been found in different studies [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations